Telecommunications demystified a streamlined course in digital communications (and some analog) for EE students and practicing engineers - Nassar, Carl, 1968-; Elsevier Science Publishers (Eagle Rock, Va. : LLH Technology Pub., 2001)
Carl R. Nassar, Ph.D., is professor of telecommunications at Colorado State University and director of the Research in Advanced Wireless Communications (RAWCom) laboratory there. He also consults for telecommunications firms and publishes extensively in the wireless literature. Balances a solid theoretical treatment of subjects with practical applications and examples. Covers both digital and analogue telecommunications systems, including digital modulation techniques. The CD accompanying the book includes MATLAB®
Introducing telecommunications -- Telecommunication networks -- A review of some important math, stats, and systems -- Source coding and decoding -- Getting It from here to there -- Channel coding and decoding [1] -- Channel coding and decoding [2] -- Trellis-coded modulation (TCM) -- Channel filtering and equalizers -- Estimation and synchronization -- Multiple access schemes -- Analog communications.
Includes bibliographical references (p. [345]-347) and index.
Keywords: Telecommunication; Electronic books